A comparative analysis on the shed vortices from the wake of finned, foam-wrapped cylinders. (23rd June 2017) - Khashehchi, Morteza; Ashtiani Abdi, Iman; Hooman, Kamel
Abstract: The wake characteristics behind a finned and a foam-wrapped circular cylinder has been compared in a study (Khashehchi et al 2014 Exp. Therm. Fluid Sci. 52 328–38) done by the Authors. In this paper, the shed vortices from the wake of the same cylinders have been studied. Shedding in a bluff body has an important effect on increasing the pressure drop downstream of the object. Here, we have used particle image velocimetry to investigate the detached vortices from the wake behind a foam-wrapped and a finned cylinder. The standard case of cross-flow over a bare cylinder, i.e. no surface extension, has also been tested as a benchmark. The experiments have been performed for Reynolds numbers 2000 based on the mean air velocity and the cylinder's outer diameter. To identify the features of each aforementioned case, linear stochastic estimation has been applied to the velocity fields. Results show that unlike the fin, adding foam to the cylinder surface increases the size of detached vortices and amplifies the core strength. Moreover, foam-wrapped cylinder in contrast to the finned one produces strong three-dimensionality. Interestingly, finned cylinder's results show less three-dimensionality compared to the bare cylinder.